APPLICATION OF MODIFIED ATMOSPHERE PACKAGING (MAP) ON FRESH FISH - Putri Wullandari; Diini Fithriani (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
Packaging has many functions, e.g. as containment, to protect products from physical damage,and from H2O, O2, and CO2 exposure, as well as to attract the consumers. Based on the technology,packaging  can  be  divided  into  3 types i.e.  passive  packaging,  active  packaging,  and smartpackaging. Modified Atmosphere Packaging  (MAP)  is the most  common  active  packaging  foundin  the market. MAP has been used  to extend  the shelf  life of several  fish such as  raw whiting  (codfamily), mackerel,  salmon  fillet, cod  fillet,  fresh bluefin  tuna  fillet,  etc. MAP which was combinedwith  freeze-chilling has been proved  to extend the shelf  life   of  raw whiting, mackerel, and  salmonfillet. MAP also  increased  cod  fillet’s  shelf  life  up  to 20  days, whiting  fillets packed  in  100% CO2and stored at 4°C temperature up to 15 days. MAP combined with antioxidant on fresh bluefin tunafillets stored at 3°C  for 18  days was able to extend products shelf  life  from 2 days  (control)  to 18days, meanwhile 100% N2 in packaging has  protective effect  on haemoglobin  and  lipid oxidation.Packaging innovations and ingenuity will continuously develop MAP  that is oriented  for consumer,enhance  the product, environmentally  responsive, friendly, and  cost effective.